Spurious transcription factor binding: Non-functional or genetically redundant? - Spivakov, Mikhail (BioEssays, 2014)
Transcription factor binding sites (TFBSs) on the DNA are generally accepted as the key nodes of gene control. However, the multitudes of TFBSs identified in genome‐wide studies, some of them seemingly unconstrained in evolution, have prompted the view that in many cases TF binding may serve no biological function. Yet, insights from transcriptional biochemistry, population genetics and functional genomics suggest that rather than segregating into ‘functional’ or ‘non‐functional’, TFBS inputs to their target genes may be generally cumulative, with varying degrees of potency and redundancy. As TFBS redundancy can be diminished by mutations and environmental stress, some of the apparently ‘spurious’ sites may turn out to be important for maintaining adequate transcriptional regulation under these conditions. This has significant implications for interpreting the phenotypic effects of TFBS mutations, particularly in the context of genome‐wide association studies for complex traits. How many transcription factor binding sites (TFBSs) detected in vivo are ‘functional’ is the subject of active debate. However, rather than dividing them into ‘functional’ and ‘spurious’, it may be more appropriate to see TFBSs' inputs to target genes as generally cumulative, with varying degrees of potency and redundancy.